2016 IEEE Haptics Symposium (HAPTICS) 2016
DOI: 10.1109/haptics.2016.7463163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tactile guidance cue mappings for emergency percutaneous needle insertion

Abstract: In severe trauma cases, rare but fatal conditions may quickly arise, requiring immediate percutaneous needle insertion to save the patient. As there is no time to wait for experts, inexperienced individuals are required to perform these procedures, often leading to complications. We propose the design of a novel vibrotacile sleeve to guide users through this task. While realization of a robust closed-loop guidance system is far from complete, we begin this project by identifying and evaluating three major guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In contrast, vibrotactile cues do not require the ground point for the external environment. The presentation of the vibrotactile cue to an end effector, such as the hand [29] or wrist [30] is more feasible than the presentation to a joint because the motion of the upper limb depends mainly on the position of a hand. However, the vibration stimuli have no directional cue, such as a force.…”
Section: Basic Concept Of a White Cane Techniques Training System Usi...mentioning
confidence: 99%
“…In contrast, vibrotactile cues do not require the ground point for the external environment. The presentation of the vibrotactile cue to an end effector, such as the hand [29] or wrist [30] is more feasible than the presentation to a joint because the motion of the upper limb depends mainly on the position of a hand. However, the vibration stimuli have no directional cue, such as a force.…”
Section: Basic Concept Of a White Cane Techniques Training System Usi...mentioning
confidence: 99%
“…Another option as previously stated is to give the haptic feedback to the surgeon. Basu et al [77] presented a robust closed-loop guidance system with haptic device. Based on their research, Rossa, Fong, et al [78] presented a design of a wristband with haptic feedback to assist surgeons to guide the steered needles.…”
Section: Manual Assisted Steeringmentioning
confidence: 99%
“…Nonsystematic review Systematic review [38] Research [39][40][41][42][43] Randomized crossover trial [42] Crossover trial [39][40][41]43] Existing methods lack realism, methods to enhance fidelity not feasible for real-time human interaction owing to computational complexity Haptic movement guidance Research [44][45][46][47][48][49][50][51][52] Demonstration only [44] Crossover trial [45,50,51] Randomized concurrent controlled trial [46,52] Psychophysics (accuracy) [47,48] Randomized crossover trial [49] Paucity of guidelines on effective feedback strategies, variability across human learners…”
Section: Reflective Haptic Feedbackmentioning
confidence: 99%
“…An alternative approach to reflective haptic feedback is guidance haptic feedback, in which the goal is not to simulate the patient's tissue properties but rather to enhance motor learning via haptic or tactile motion cues-cues that become critical in human-robot collaborative environments. Studies have shown the effectiveness of haptic feedback in developing motor skills [44][45][46] and guiding movement [47][48][49]. A common type of training of motor skills with haptic feedback involves recording an expert's movements and having a novice follow those movements, with haptic feedback provided if they deviate from the intended path [50].…”
Section: Physical Reality: Evaluation Of Feedback Effectivenessmentioning
confidence: 99%